Contemporary mission theology : engaging the nations : essays in honor of Charles E. van Engen - Gallagher, Robert L.; Hertig, Paul, 1955-; Engen, Charles Edward van. (New York : Orbis Books, 2017)
A resource for the classroom that specifically addresses the missiological issues of the twenty-first century, this collection in honor of Charles E. Van Engen features contributions from practically all the leading lights of the missiology world, offering their insights and reflections, focusing on the impact of cultural and demographic changes on the nature and purpose of Christian mission. (Publisher)
Biography of Charles E. Van Engen -- Introduction / Paul Hertig -- The emergence of mission theology / Jan A. B. Jongeneel -- A new missionary age / Gerald H. Anderson -- Part 1: Mission theology and the Bible. The Biblical story of narrative theology / Michael W. Goheen -- Contextual Christology: carrying the Great Commission with joy / David Hartono -- Mission theology in the city: sowing urban seeds of Shalom / Stephen E. Burris -- Part 2: Mission theology and church beliefs. Missionary ecclesiology: Evangelical, ecumenical, and Catholic developments in "engaging the nations" / Stephen B. Bevans, S.V.D., and Roger P. Schroeder, S.V.D. -- Missionary theology: Roland Allen and Vincent Donovan rediscovered / J. Andrew Kirk -- Mission theology and the nature of God / J. N. J. (Klippies) Kritzinger -- Part 3: Mission theology in context. Carlitos de Las Casas: a theologian made in Latin America / Antonio Carlos Barro and Jorge Henrique Barro -- Recovering reconciliation as God's mission: its implications for North and South Korea / Kyung Lan Suh -- Redeeming mission theology in Africa: a Congolese perspective toward resolving ethnic conflict / Mossai T. Sanguma -- Part 4: Mission theology and the church. Matthew's Experience of Discipleship and the Great Commission / Paul Hertig -- Missionary churches in Acts: a model of intercultural engagement with the nations / vanThanh Nguyen, S.V.D. -- Group identities and boundaries during the Pauline mission / Adam D. Ayers -- Part 5: Mission theology and church history. Historical perspectives on Catholic mission theology / Mary Motte, F.M.M. -- Historical perspectives on Protestant mission theology: striving toward a new model for a postmodern context / Pablo A. Deiros -- Historical perspectives on Pentecostal mission theology / DeLonn L. Rance -- Part 6: Mission theology and religious pluralism. Good news for all people: engaging Luke's narrative soteriology of the nations / Robert L. Gallagher -- Interfaith education and the Missio Dei: a case study in the Pacific Northwest / Sarita D. Gallagher -- Interreligious dialogue and convivence: missional challenge and charge for today / Jerald D. Gort -- Part 7: Modernity and postmodernity in mission theology. Mission theology and stewardship of the Earth / Young Lee Hertig -- Korean Women Missionaries: Agents of God's Mission / Bokyoung Park -- Mission theology and postmodern social networks / Shawn B. Redford -- Part 8: Mission theology and ministry formation. Engaging the nations in Los Angeles: a spirituality of accompaniment / Jude Tiersma Watson -- Carrying heavy stories: discerning what the body carries / Mary Thiessen Nation -- Reaping missionary leaders in the college years / Christina Tellechea Accornero -- Conclusion: seeking ways forward in mission theology / Charles E. Van Engen.
Includes bibliographical references and index.
Keywords: Engen, Charles Edward van; Missions -- Theory; Missions; Missions; Missions -- Theory